Rhizopus-associated soft tissue infection in an immunocompetent air-conditioning technician after a road traffic accident: A case report and review of the literature - Nada B. Rabie; Abdulhakeem O. Althaqafi (Elsevier, 2012)
Summary: Rhinocerebral or sinopulmonary mucromycosis is a well-recognized human fungal infection found among immunocompromised and diabetic patients. However, the infection is rare among immunocompetent hosts. We are reporting the case of an adult immunocompetent male patient working as an air-conditioning technician. The patient was a victim of a road traffic accident (RTA) and sustained multiple fractures in the proximal part of the left tibia, distal femur, and scapula. Two weeks postoperatively, Rhizopus microspores were isolated from an infected traumatic wound over the distal femur. Surgical debridement was performed, and the patient was started on amphotericin B. Occupational exposure history and workplace environmental sanitation are crucial for the prevention of this potentially fatal yet preventable infection. Keywords: Rhizopus, Immunocompetent, Air conditioning